Morpho-anatomical description of new Begonia species (sect. Baryandra, Begoniaceae) from Butuan City, Mindanao Island, Philippines - Bucay, Mark Angelo C.; Tandang, Danilo N.; Chen, Hong-Wun; Rubite, Rosario R.; Chung, Kuo-Fang (Phytotaxa, 2025)
Begonia butuanensis, a new species of Begonia sect. Baryandra endemic in northeastern Mindanao is described. We compared it to another species endemic to southern Mindanao, B. copelandii. Both species have ciliate leaf margins, rounded outer tepals, and lanceolate inner tepals of staminate flowers. However, B. butuanensis is distinct in its smaller perianth size, triangular capsule lateral wing with subfalcate apex (vs. rectangular with subacute to truncate apex in B. copelandii), puberulous peduncles (vs. glabrous), and orbicular to slightly ovate lamina with rounded to obtuse apices (vs. ovate to orbicular lamina with obtuse to acuminate apex). The species is observed only from the type locality, and we recommend the species to be listed as Critically Endangered (CR) following the 2024 IUCN guidelines.